2018
DOI: 10.1038/s41598-018-29500-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of the catalytic mechanism of Plasmodium CCT, a key enzyme of malaria lipid biosynthesis

Abstract: The development of the malaria parasite, Plasmodium falciparum, in the human erythrocyte, relies on phospholipid metabolism to fulfil the massive need for membrane biogenesis. Phosphatidylcholine (PC) is the most abundant phospholipid in Plasmodium membranes. PC biosynthesis is mainly ensured by the de novo Kennedy pathway that is considered as an antimalarial drug target. The CTP:phosphocholine cytidylyltransferase (CCT) catalyses the rate-limiting step of the Kennedy pathway. Here we report a series of struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…An 18 amino acid-long, lysine-rich insertion is present in the catalytically important L5 loop in both the first and second catalytic domains (C1 and C2) of Pf CCT, respectively 11 . The L5 loop is responsible for the coordination of the quaternary ammonium moiety of choline with residues Y131/Y714, N133/N716 and Y158/Y741 in C1/C2 and contributes to the formation of the composite aromatic box cleft 43 , 44 . We generated a homology model of Pf CCT to complete the recently resolved crystal structure (PDB: 4ZCS, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An 18 amino acid-long, lysine-rich insertion is present in the catalytically important L5 loop in both the first and second catalytic domains (C1 and C2) of Pf CCT, respectively 11 . The L5 loop is responsible for the coordination of the quaternary ammonium moiety of choline with residues Y131/Y714, N133/N716 and Y158/Y741 in C1/C2 and contributes to the formation of the composite aromatic box cleft 43 , 44 . We generated a homology model of Pf CCT to complete the recently resolved crystal structure (PDB: 4ZCS, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We generated a homology model of Pf CCT to complete the recently resolved crystal structure (PDB: 4ZCS, Fig. 2 B) 44 by visualizing the 720–737 Lys-rich insertion that was deleted from the crystallized construct. The insertion appears as a highly flexible region, characterized by low QMEAN local quality scores with an average of 0.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7B). Guca et al (19) had found evidence for phosphocholine-independent PP i production by a catalytically compromised K122A analog in the CCT from P. falciparum, suggesting that CTP hydrolysis might in some cases be a competing reaction for the cytidyl transfer reaction. A hydrolysis potential has never been established for CCT, but it could explain why, for example, the soluble form and CCT-236 have such high apparent K m values for CTP.…”
Section: Probing a Mechanism For Catalytic Enhancement By A Membrane-mentioning
confidence: 99%
“…An alternative hypothesis for enhanced catalytic function is that a relatively anhydrous active site would strengthen the charge-charge interactions between enzyme and substrates. The CCT active site provides multiple amine-containing residues that overcome the repulsive negative charges between the substrates, CTP and phosphocholine (19,20) (Fig. 7A).…”
Section: Probing a Mechanism For Catalytic Enhancement By A Membrane-mentioning
confidence: 99%